Carbon Fluxes and Microbial Activities From Boreal Peatlands Experiencing Permafrost Thaw. Issue 3 (26th March 2021) - Waldrop, M. P.; W. McFarland, J.; Manies, K. L.; Leewis, M. C.; Blazewicz, S. J.; Jones, M. C.; Neumann, R. B.; Keller, J. K.; Cohen, L.; Euskirchen, E. S.; Edgar, C.; Turetsky, M. R.; et al.
Abstract: Permafrost thaw in northern ecosystems may cause large quantities of carbon (C) to move from soil to atmospheric pools. Because soil microbial communities play a critical role in regulating C fluxes from soils, we examined microbial activity and greenhouse gas production soon after permafrost thaw and ground collapse (into collapse‐scar bogs), relative to the permafrost plateau or older thaw features. Using multiple field and laboratory‐based assays at a field site in interior Alaska, we show that the youngest collapse‐scar bog had the highest CH4 production potential from soil incubations, and, based upon temporal changes in porewater concentrations and 13 C‐CH4 and 13 C‐CO2, had greater summer in situ rates of respiration, methanogenesis, and surface CH4 oxidation. These patterns could be explained by greater C and N availability in the young bog, while alternative terminal electron accepting processes did not play a significant role. Field diffusive CH4 fluxes from the young bog were 4.1 times greater in the shoulder season and 1.7–7.2 times greater in winter relative to older bogs, but not during summer. Greater relative CH4 flux rates in the shoulder season and winter could be due to reduced CH4 oxidation relative to summer, magnifying the importance of differences in production. Both the permafrost plateau and collapse‐scar bogs were sources of C to the atmosphere due in large part to winter C fluxes. In collapse scar bogs, winter is a critical period when differences in thermokarst age translates to differences in surface fluxes. Plain Language Summary: Permafrost thaw is occurring in Alaska which may result in a positive feedback to climate warming, due to the release of greenhouse gases such as CO2 and CH4 from soils. Here we examined greenhouse gas production along a gradient of "time since thaw, " hypothesizing that fluxes and microbial activities would be highest soon after thaw, and then decline. We observed highest rates of microbial activities, particularly methanogenesis, soon after thaw, coinciding with less decomposed organic matter and higher concentrations of dissolved carbon and nitrogen in soil, possibly of permafrost origin. However, field fluxes were higher in the young thaw site, compared to the older sites, in winter and not summer, a phenomenon that is currently not well understood. Key Points: Permafrost thaw chronosequence shows methanogenic activity highest soon after thaw and then declines over decades Greater methanogenic activity in young collapse scar bogs results in higher winter, but not summer, fluxes Increased methanogenic activity is plausibly tied to increased dissolved organic carbon and nitrogen in young collapse scar bog soils